2011
DOI: 10.1063/1.3562574
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of instability enhanced collisional friction for determining ion loss in two ion species plasmas

Abstract: Recent experiments have shown that ions in weakly collisional plasmas containing two ion species of comparable densities approximately reach a common velocity at the sheath edge equal to the bulk plasma ion sound velocity. A recent theory [S. D. Baalrud, C. C. Hegna, and J. D. Callen, Phys. Rev. Lett. 103, 205002 (2009)] suggests that this is a consequence of collisional friction between the two ion species enhanced by the two stream instability. The theory finds that the difference in velocities at the shea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 19 publications
6
44
0
Order By: Relevance
“…It also includes determining a T e /T i threshold for instability in a presheath by setting ∆V = |c s1 − c s2 |. Figure 8 provides a further quantification of the stability boundaries for Ar + -Xe + and He + -Xe + mixtures, which are common in experiments [10,11]. This shows the stability boundary for the critical differential flow ∆V c at several values of T e /T i .…”
Section: Two Ion Speciesmentioning
confidence: 99%
“…It also includes determining a T e /T i threshold for instability in a presheath by setting ∆V = |c s1 − c s2 |. Figure 8 provides a further quantification of the stability boundaries for Ar + -Xe + and He + -Xe + mixtures, which are common in experiments [10,11]. This shows the stability boundary for the critical differential flow ∆V c at several values of T e /T i .…”
Section: Two Ion Speciesmentioning
confidence: 99%
“…Several experiments [2,[4][5][6] have shown that when the densities of Ar þ and Xe þ are similar, the speed of Ar þ is significantly slower than its sound speed, and the speed of Xe þ is significantly faster than its sound speed. The most recent experiments [5,6] have shown that the density ratio of ion species is also important. When the density ratio is large or small, individual sound speeds are measured, but when the ratio is near unity, the speeds merge toward the system sound speed.…”
mentioning
confidence: 99%
“…The theory uses this threshold and the generalized Bohm criterion to determine the speed of each species at the sheath edge [8]. The theoretical predictions have been tested experimentally in both Ar=Xe [5] and He=Xe [6] plasmas. In both cases, good agreement is found over a broad range of ion density ratios.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31] One of the elegant results in plasma physics is the Bohm criteria [32] that define the minimal speed with which the positive ions enter the sheath boundary. Although the Bohm speed was originally derived for electropositive plasmas, its significance in multi-component plasmas including negative ions [33][34][35] has been comprehended both theoretically and via experiments. A significant number of theoretical/experimental studies on sheath/pre-sheath behaviour have been largely devoted to negative ions produced in the bulk plasma.…”
Section: Introductionmentioning
confidence: 99%